Phosphoglycerolipids are master players in plant hormone signal transduction - Janda, Martin; Planchais, Severine; Djafi, Nabila; Martinec, Jan; Burketova, Lenka; Valentova, Olga; Zachowski, Alain; Ruelland, Eric (Plant cell reports, 2013)
Phosphoglycerolipids are essential structural constituents of membranes and some also have important cell signalling roles. In this review, we focus on phosphoglycerolipids that are mediators in hormone signal transduction in plants. We first describe the structures of the main signalling phosphoglycerolipids and the metabolic pathways that generate them, namely the phospholipase and lipid kinase pathways. In silico analysis of Arabidopsis transcriptome data provides evidence that the genes encoding the enzymes of these pathways are transcriptionally regulated in responses to hormones, suggesting some link with hormone signal transduction. The involvement of phosphoglycerolipid signalling in the early responses to abscisic acid, salicylic acid and auxins is then detailed. One of the most important signalling lipids in plants is phosphatidic acid. It can activate or inactivate protein kinases and/or protein phosphatases involved in hormone signalling. It can also activate NADPH oxidase leading to the production of reactive oxygen species. We will interrogate the mechanisms that allow the activation/deactivation of the lipid pathways, in particular the roles of G proteins and calcium. Mediating lipids thus appear as master players of cell signalling, modulating, if not controlling, major transducing steps of hormone signals.
Keywords: fosfolipasy; Plant Proteins; Phosphotransferases; Phospholipases; signální transdukce; Signal Transduction; rostliny; rostlinné proteiny; Phosphatidic Acids; kyseliny fosfatidové; kyselina abscisová; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; glycerofosfolipidy; Plants; Abscisic Acid; Arabidopsis; transkriptom; fosfotransferasy; regulátory růstu rostlin; Transcriptome; Glycerophospholipids; Plant Growth Regulators